2022
DOI: 10.1002/ps.7288
|View full text |Cite
|
Sign up to set email alerts
|

Considering degradation kinetics of pesticides in plant uptake models: proof of concept for potato

Abstract: BACKGROUND: Degradation kinetics of pesticides in plants are crucial for modeling mechanism-based pesticide residual concentrations. However, due to complex open-field conditions that involve multiple pesticide plant uptake and elimination processes, it is difficult to directly measure degradation kinetics of pesticides in plants. To address this limitation, we proposed a modeling approach for estimating degradation rate constants of pesticides in plants, using potato as a model crop. An operational tool was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 66 publications
(234 reference statements)
0
4
0
Order By: Relevance
“…Biodegradation is of particular importance for mostly ionized chemicals due to their slow uptake into organisms (Carter et al, 2022). Because of the lack of data, degradation rates in plants are often neglected (Jacobsen et al, 2015; Li & Fantke, 2022), which leads to bioconcentration predictions at the upper end of measured ones (Polesel et al, 2015). The average of dissipation half‐life of loss data from plants collected by Fantke and Juraske (2013) was 7 days, which corresponds to the default growth dilution rate used for roots and corn (0.1 day −1 ) in the PPCP model.…”
Section: Discussionmentioning
confidence: 99%
“…Biodegradation is of particular importance for mostly ionized chemicals due to their slow uptake into organisms (Carter et al, 2022). Because of the lack of data, degradation rates in plants are often neglected (Jacobsen et al, 2015; Li & Fantke, 2022), which leads to bioconcentration predictions at the upper end of measured ones (Polesel et al, 2015). The average of dissipation half‐life of loss data from plants collected by Fantke and Juraske (2013) was 7 days, which corresponds to the default growth dilution rate used for roots and corn (0.1 day −1 ) in the PPCP model.…”
Section: Discussionmentioning
confidence: 99%
“…From a risk and impact assessment perspective and due to data constraints, these models typically omit the biodegradation or biotransformation processes of pesticides within potato tissue. 47 However, our study deviates from this approach by incorporating such processes, as our primary focus centers on considering the generation of pesticide metabolites. Both soil and potatoes are involved in the transformation of the parent compound into metabolites.…”
Section: General Model For Potato Uptake Of Metabolitesmentioning
confidence: 99%
“…Song et al (2023) in his review demonstrated that biochar has high adsorption potential and can accelerate the pesticide degradation of soil and mitigate its uptake in the plantings. Therefore, biochar application in pesticide-contaminated soil can be a good option for minimizing the risk associated with the consumption of contaminated agricultural produce (Li and Fantke 2023;Song et al 2023).…”
Section: Introductionmentioning
confidence: 99%